Avaliação da Efetividade de Gestão do Parque Nacional de Ubajara - Ce - Cunha, Bartolomeu Bueno (2010)
The research project was developed in the park Ubajara (PNU) - conservation unit established in 1959 and enlarged in 2002 - with the overall objective of evaluating the effectiveness of management, using the method RAPPAM and having specific objectives are to analyze the main pressures and threats in PNU and analyze the attitudes of residents of the surrounding area with respect to the Park. For this, we carried out field work for questionnaires, photographic survey, interviews to obtain information that would permit the profiles of the surrounding residents, to evaluate the effectiveness of management and context analysis identifying the main pressures and threats impact the PNU. The results show that the PNU has a level of effectiveness of management and unsatisfactory, although very vulnerable to pressures and threats against its environmental integrity, 71.1% of the analyzed factors presents a low level of criticality. The profile of residents surrounding the PNU, appears to be well varied mostly farmers with small farms mostly showing a level of real income over four hundred each month and receive some assistance from the federal government. According to residents of the surrounding area there is a very frequent dialogue with officials of PNU, this information could be confirmed, because the majority of respondents claimed to know the location and size of the PNU, but there is some commitment from communities with environmental conservation, because when asked about or use the area for agriculture and permission to hunt the majority disagrees. As the discussion made, the results of this research can contribute significantly in the search for improved management of PNU, analyze the profile of the surrounding residents and assist in developing partnerships between communities and officials of PNU seeking greater effectiveness in managing the area.